Pengaruh Pendekatan Culturally Responsive Teaching Dengan Model Project Based Learning Terhadap Hasil Belajar Ppkn Siswa Smp Negeri 1 Baitussalam - Yubida Syarwani , Viona (Universitas Pendidikan Ganesha, 2024)
Civics (PPKn) plays a strategic role in shaping students’ character and civic awareness, yet classroom practice often remains teacher-centered, limiting conceptual understanding and real-life transfer. This study examines the effect of a culturally responsive teaching (CRT) approach combined with project-based learning (PBL) on PPKn learning outcomes at SMP Negeri 1 Baitussalam. A quasi-experimental pretest–posttest control group design was employed. The population comprised all Grade VII students; samples were selected purposively with class VII-1 as the experimental group (CRT+PBL) and VII-2 as the control group. Learning outcomes were measured using 10 multiple-choice and 5 essay items administered at pretest and posttest. Data were analyzed with an independent samples t-test. Results show t_calculated=2.105 exceeding t_table=1.672, leading to rejection of H₀ and acceptance of Hₐ; thus, the CRT–PBL intervention had a significant positive effect on PPKn learning outcomes. The findings suggest that culturally responsive, project-oriented instruction strengthens conceptual mastery and connects content to authentic contexts. Practically, teachers are encouraged to integrate CRT–PBL within lesson planning and authentic assessment, supported by ongoing professional development. Future research should use larger and more diverse samples and examine impacts on retention, civic attitudes, and 21st-century skills.